1976
DOI: 10.1128/iai.13.5.1483-1489.1976
|View full text |Cite
|
Sign up to set email alerts
|

Pili as a mediator of the attachment of gonococci to human erythrocytes

Abstract: Isolated pure gonococcal pili were found capable of producing direct agglutination of human erythrocytes. Four different strains of gonococci were compared, and hemagglutination was produced by isolated pili or piliated gonococci but not by nonpiliated gonococci of each strain. Pili from each of the four strains were antigenically distinguishable using antisera specific for pili to agglutinate piliated gonococci, form precipitin lines in Ouchterlony immunodiffusion, or inhibit hemagglutination caused by purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 10 publications
(12 reference statements)
0
29
1
Order By: Relevance
“…Previous studies suggested that pili were responsible for the attachment of meningococci and gonococci to erythrocytes (6,16,26,37). However, we found strain-to-strain variation among piliated meningococci with respect to erythrocyte attachment.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies suggested that pili were responsible for the attachment of meningococci and gonococci to erythrocytes (6,16,26,37). However, we found strain-to-strain variation among piliated meningococci with respect to erythrocyte attachment.…”
Section: Discussioncontrasting
confidence: 75%
“…We have recently shown (unpublished data) that the bacterial hemagglutination of human erythrocytes is resistant to inhibition by 0.5% D-mannose, whereas the hemagglutination of chicken erythrocytes is susceptible to inhibition by D-mannose. It should be noted that the hemagglutination of erythrocytes by common pili of E. coli is inhibited by D-mannose (5), whereas the hemagglutination of erythrocytes by virulence-associated cellular appendages such as K88 or pili of gonococci is D-mannose insensitive (1,8).…”
Section: Discussionmentioning
confidence: 99%
“…Thus it would appear that gonococci, like other bacteria, may be able to attach to host cells by means of surface factors other than pili (4,16,18,19). Nonetheless, pili have been postulated to promote virulence by enhancing attachment to host cells (1,6,11,13,22), and in this respect it is interesting to note the profuse occurrence of long pili on pathogenic neisseria in contrast to the sparse occurrence of long pili on nonpathogenic neisseria. However, even if pili do aid in attachment of gonococci to host cells, attachment alone does not explain the damage to host cells that follows.…”
Section: Discussionmentioning
confidence: 99%